PENGARUH BRAND IMAGE DAN BRAND AWARENESS LAZADA TERHADAP KEPUTUSAN PEMBELIAN ONLINE - Astuti, Ni Luh Gde Sari Dewi; Widhyadanta, I Gde Dirga Surya Arya; Sari, Retno Juwita (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.10.TAHUN.2021DO - 10.24843/EEB.2021.v10.i10.p07, 2021)
During the pandemic, the government regulates restrictions on activities in public places or facilities. Including buying daily necessities. As a result of this restriction, people make purchases online to buy all household needs as an anticipation and inventory measure. This study aims to determine the effect of brand image and brand awareness on purchasing decisions on consumers who shop online using the Lazada marketplace. The method of collecting data through a google form questionnaire was distributed to 100 respondents to consumers who shop at Lazada. This study found that brand image has a positive and significant effect on purchasing decisions. Brand awareness has a positive and significant effect on purchasing decisions. Brand image and brand awareness have a simultaneous and positive effect on purchasing decisions.